A rare case report of progressive symmetric erythrokeratoderma in five generations of an Indian family - Gupta, Anil Kumar; Kaushik, Kanishk Utkarsh; ., Sushantika; Sachan, Shivangi (International Journal of Research in Dermatology, 2018)
Erythrokeratoderma is a rare group of disorders of autosomal dominant inheritance characterised by localised erythema and hyperkeratosis. Within a broad spectrum of phenotypes atleast two are delineated: a) Erythrokeratoderma variabilis and b) Progressive symmetric erythrokeratoderma. Here we are reporting a case of progressive symmetric erythrokeratoderma in an Indian family where five successive generations were involved.